School Administrative Staff: Duties and Responsibilities in Modern Education - Abdullah, Muhammad Ridwan; Arifin, Imron (Proceedings Series of Educational Studies, 2024)
In this context, this article will discuss in depth the various duties and responsibilities of school administrators in the modern education era. By understanding these duties and responsibilities, it is hoped that educational administrators can optimize the education system. This research uses the library research method, which focuses on analyzing literature and secondary sources relevant to the research topic. Researchers collected and reviewed various sources of information such as books, scientific journals and research reports related to the research topic. Administrative personnel play an important role in improving school administrative services and developing school quality improvement with several activities carried out. School administrative personnel are tasked with providing administrative service support for the implementation of the educational process at school. Their duties and responsibilities include various aspects that are all interrelated to create an optimal learning environment and as a liaison between various parties in the school, for effective communication.